Effect of Hormone Concentration and frequency of administration of Gibberellins on Growth and Yield of Tomato Fruit - Hardiyanti Tiyas Ning; Sundahri; Setiyono; Gatot Subroto (Faculty of Agriculture, Merdeka University Surabaya, 2018)
The aim of this research was to identify the influence of giberellin hormone concentration and its application frequency on the growth and the yield of tomato fruit. This research had been undertaken at Agrotechnopark, the University of Jember 6 November 2017 - 10 February 2018. The experiment using randomized complete block design (RCBD) with two factors namely the concentration of giberellin hormone consisted of 4 levels (0 ppm, 50 ppm, 75 ppm, 100 ppm) and the second was its frequency application consisted of three levels (spraying once every 7 days, 14 days, and 21 days). Reviews These were arranged in a factorial design and each combination was repeated by three times. The results Showed that (1) siqnificantly influenced concentrations of hormone on the growth and the yield of tomatoes. (2) the frequency of its application on the number affected siqnificantly productive branches, the number and weight of fruit, the weight of the tomato fruit. (3) there was no interaction of giberellin and its aplication on all paramters. (4) the best treatment is G3F3, the gibereellin concentration of 100 ppm and the frequency of 21 days once.